2018
DOI: 10.1101/426213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional heterogeneity in gene expression, regulation and coherence in hippocampus and dorsolateral prefrontal cortex across development and in schizophrenia

Abstract: Recent large-scale genomics efforts have better characterized the molecular correlates of schizophrenia in postmortem human neocortex, but not hippocampus which is a brain region prominently implicated in its pathogenesis. Here in the second phase of the BrainSeq Consortium (Phase II), we have generated RiboZero RNA-seq data for 900 samples across both the dorsolateral prefrontal cortex (DLPFC) and the hippocampus (HIPPO) for 551 individuals (286 affected by schizophrenia disorder: SCZD). We identify substanti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 62 publications
1
17
1
Order By: Relevance
“…We lastly explored unique illness state-associated gene expression differences in the DG-GCL compared to the bulk hippocampus. Our previous work suggested that the hippocampus had fewer genes differentially expressed in samples from patients with schizophrenia compared to genes differentially expressed between patients and controls in the DLPFC (both using ribosomal-depletion sequencing methods) 9 . In the DG-GCL, we similarly found relatively small numbers of genes associated with diagnosis, particularly compared to aging and eQTL effects.…”
Section: Unique Signatures Of Illness In the Dg-gclmentioning
confidence: 99%
See 4 more Smart Citations
“…We lastly explored unique illness state-associated gene expression differences in the DG-GCL compared to the bulk hippocampus. Our previous work suggested that the hippocampus had fewer genes differentially expressed in samples from patients with schizophrenia compared to genes differentially expressed between patients and controls in the DLPFC (both using ribosomal-depletion sequencing methods) 9 . In the DG-GCL, we similarly found relatively small numbers of genes associated with diagnosis, particularly compared to aging and eQTL effects.…”
Section: Unique Signatures Of Illness In the Dg-gclmentioning
confidence: 99%
“…GRM3) are classic therapeutic drug targets and eQTLs for these genes in bulk tissue have been elusive. We explored the tissue specificity of these eQTLs using the BrainSeq DLPFC 8,9 , CommonMind Consortium DLPFC 3 and GTEx 5 bulk tissue projects. The GWAS index SNP that associated with GRM3 expression (rs12704290) was not significantly associated with any expression features in the BrainSeq or CommonMind Consortium DLPFC, or GTEx datasets across any brain region or body tissue.…”
Section: Cell Type Specific Eqtls For Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations